Bypassing Barriers: Surface-Groundwater Exchange Between a Wetland, Sandur, and Lava Field in Southeastern Iceland - Aggarwal, Aiesha Katya (2021)
Iceland is expected to experience slight increases in temperature, precipitation, glacial melt, and volcanic activity over the next century. The influence this will have on groundwater recharge and discharge in spring-fed ecosystems cannot be predicted without a better understanding of spring geological framework and their hydrological regimes. In May 2019, over 50 springs were identified at a sandur-lava field-wetland complex in Southeast Iceland and a subset was selected for further investigation. Spot measurements of water chemistry during the May 2019 field season revealed that the springs discharged cold (45C), slightly acidic (pH 6.16.7) freshwater. Between May 2019 and September 2019, springs at the study site had relatively stable water levels and temperatures, although heavy rains (> 10 mm) corresponded with increased water level and/or temperatures at some locations. Long-term studies will be needed to gain an improved understanding of seasonal spring vulnerability to climate change.